Електронна мішень в радіоелектронному пристрої для тренування біатлоністів - Нікулкін, В. О.; Чобану, П. В. (My University, 2018)
Biathlon is one of the few sports, the winner in which is determined by a combination of two indicators: the speed of the distance and the effectiveness of the shooting. For achievement of high results in modern sports it is necessary to have highly effective, technically equipped base for trainings.
Keywords: тренажер; мішень